Optical coherence tomography angiography suggests different retinal pathologies in multiple sclerosis and Sjögren’s syndrome - Wolf, Elisabeth; Wicklein, Rebecca; Aly, Lilian; Schmaderer, Christoph; Afzali, Ali Maisam; Mardin, Christian; Korn, Thomas; Hemmer, Bernhard; Hofauer, Benedikt; Knier, Benjamin (Journal of Neurology, 2024)
Background: While retinal vessel changes are evident in the eyes of patients with relapsing–remitting multiple sclerosis (RRMS), changes in the vasculature of possible MS mimics such as primary Sjögren’s syndrome (pSS) remain to be determined. We investigated the potential of retinal optical coherence tomography (OCT) angiography (OCTA) as diagnostic tool to differentiate between patients with RRMS and pSS. Methods: This cross-sectional study included patients with RRMS (n = 36), pSS (n = 36) and healthy controls (n = 30). Participants underwent clinical examination, assessment of visual acuity, retinal OCT, OCTA, and serum markers of glial and neuronal damage. We investigated the associations between OCTA parameters, visual functions, and serum markers. Eyes with a history of optic neuritis (ON) were excluded from analysis. Results: We observed a significant thinning of the combined ganglion cell and inner plexiform layer in the eyes of patients with RRMS but not with pSS, when compared to healthy controls. Retinal vessel densities of the superficial vascular complex (SVC) were reduced in both patients with RRMS and pSS. However, retinal vessel rarefication of the deep vascular complex (DVC) was only evident in patients with pSS but not RRMS. Using multivariate regression analysis, we found that DVC vessel loss in pSS patients was associated with worse visual acuity. Conclusions: Compared to patients with RRMS, rarefication of deep retinal vessels is a unique characteristic of pSS and associated with worse visual function. Assuming a disease-specific retinal vessel pathology, these data are indicative of a differential affliction of the gliovascular complex in the retina of RRMS and pSS patients.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Differential diagnosis; Multiple sclerosis (MS); Optical coherence tomography angiography (OCTA); Sjöegren’s syndrome